Ecological momentary assessment of stress, racism and other forms of discrimination during pregnancy using smartphone technology. Issue 5 (13th January 2020) - Mendez, Dara D.; Sanders, Sarah A.; Lai, Yu‐Hsuan; Wallace, Meredith L.; Rathbun, Stephen L.; Gary‐Webb, Tiffany L.; Davis, Esa M.; Burke, Lora E.
Abstract: Background: In the United States, there are considerable racial inequities in adverse perinatal outcomes. Exposure to racism, sexism, and other forms of oppression may help explain these inequities. Objectives: To describe the application of real‐time data collection using ecological momentary assessment (EMA) and smartphone technology to assess exposure to stress, racism, sexism, microaggressions, and other forms of oppression. Methods: The Postpartum Mothers Mobile Study (PMOMS) is an ongoing longitudinal cohort study that began recruitment in December 2017. Participants delivering at a hospital in Pittsburgh, PA are recruited by 29 weeks' gestation. Using smartphones and smart scales, participants complete daily surveys related to psychosocial, behavioural, and contextual factors and weigh themselves weekly for approximately 15 months. We provide a preliminary descriptive analysis of EMA self‐reported measures of stress, racism, sexism, and microaggressions; and non‐EMA measures of stress and major discrimination. Results: The sample (n = 230) is 63.5% White, 24.8% Black/African American, and 7% Hispanic origin. The most commonly reported item from the Major Discrimination Scale is being unfairly fired (18.1% of the sample). Of those, 31.7% and 17.1% attribute unfair firing to their gender and race, respectively. From the random EMA measures, on average, participants report experiences of racism and sexism at least once daily, in an average 12‐hour day over the 4‐week period. Black participants indicate about two experiences per day of racism, and White participants indicate more than 1 per day of sexism. Mean stress levels from the EMA measures were similar to the stress measures collected at baseline. Conclusions: The methods applied in PMOMS provide real‐time data regarding how participants' daily experiences of stress and discrimination influence their lives. Future work will include understanding if and how these EMA measures may relate to already established measures of racism, sexism, and stress; and ultimately understanding associations with perinatal inequities.